Asking the experts: Indigenous educators as leaders in early education and care settings in Australia - Locke, Michelle (The Australian Journal of Indigenous Education, 2022)
The educational rationale behind the inclusion of Indigenous knowledges and perspectives in early education and care services in Australia is grounded in effective engagement and support of Indigenous families. Additionally, this inclusion aims to promote non-Indigenous understanding and recognition of Indigenous peoples, with a view to strengthening reconciliation and improving outcomes for Indigenous children. However, a lack of confidence and capacity of a largely non-Indigenous early childhood educator cohort has resulted in either the absence or misrepresentation of Indigenous knowledges and/or perspectives. This paper presents research that identifies Indigenous peoples as the owners and experts of Indigenous knowledges and perspectives. Employing a qualitative approach from within an Indigenous methodological framework, the research engaged the expertise of Indigenous educators to identify and recruit additional research participants. From this research, it is clear that specific characteristics related to knowledge, experience and understanding position Indigenous educators as the most valuable and capable leaders in the inclusion of Indigenous knowledges and perspectives in early education and care settings.